Pendampingan BUMDesa : Peran Strategis Bumdes Dan Revitalisasi Ekonomi Desa Di Kabupaten Karanganyar,Klaten, dan Sukoharjo - Kurniawan, Itok Dwi; Ismawati Septiningsih (Jurnal Atma Inovasia, 2024)
BUMDes as a village-managed business institution has a strategic role in efforts to improve the village economy. However, unfortunately, there are still very few villages that are able to optimize the role of BUMDes, so that many BUMDes are "in suspended animation" and are not developing. For this reason, revitalization measures are needed for existing BUMDes. For example, in several BUMDes in the Karanganyar, Klaten and Sukoharjo areas. This is important because the BUMDes revitalization process ultimately seeks to make the village a competitive village. The location of the activity was held at the LPPM Building, Sebelas Maret University. The methods that will be used in this activity are through lectures, discussions, focus group discussions, and mentoring. The results of this activity show that understanding regarding the strategic role of BUMDes and the revitalization of the village economy has increased. Apart from that, BUMDes administrators in the Karanganyar, Klaten and Sukoharjo areas can be more enthusiastic and optimistic in carrying out BUMDes activities.